2013
DOI: 10.1126/scitranslmed.3006007
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Wave Activity Saturation and Thalamocortical Isolation During Propofol Anesthesia in Humans

Abstract: The altered state of consciousness produced by general anesthetics is associated with a variety of changes in the brain's electrical activity. Under hyperpolarizing influences such as anesthetic drugs, cortical neurons oscillate at ~1 Hz, which is measurable as slow waves in the electroencephalogram (EEG). We have administered propofol anesthesia to 16 subjects and found that, after they had lost behavioral responsiveness (response to standard sensory stimuli), each individual's EEG slow-wave activity (SWA) ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
170
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(194 citation statements)
references
References 40 publications
20
170
3
1
Order By: Relevance
“…Previous studies in humans have observed significant increases in slow oscillation power during loss of consciousness (7,12) and have established that these oscillations correspond to ON and OFF states where neurons are periodically silenced (11). Notably, unlike propofol-induced α waves, these slow oscillations are spatially incoherent (7,11), implying a state of "fragmentation" of cortical activity (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in humans have observed significant increases in slow oscillation power during loss of consciousness (7,12) and have established that these oscillations correspond to ON and OFF states where neurons are periodically silenced (11). Notably, unlike propofol-induced α waves, these slow oscillations are spatially incoherent (7,11), implying a state of "fragmentation" of cortical activity (11).…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalogram (EEG) recordings in humans during gradual induction of unconsciousness with propofol show the appearance of frontal β oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at the onset of sedation, followed by the appearance of coherent frontal α (8-12 Hz) oscillations (7)(8)(9)(10) and widespread slow (0.1-1 Hz) and δ (1-4 Hz) oscillations (7,11,12) when subjects no longer respond to sensory stimuli. Biophysical models of neuronal dynamics have shown that whereas α and β oscillations can be generated by propofol's actions in cortex alone (13), coherent α oscillations require the participation of both thalamus and cortex (14).…”
mentioning
confidence: 99%
“…electrophysiology or brain imaging technologies [17,18]. However, if as discussed above, several different brain states are compatible with 'anaesthesia' (including some that involve degrees of awareness), then it follows that all anaesthetic drugs do not necessarily produce the same pattern of neuronal activity, but potentially induce their own, distinct patterns.…”
Section: The Implications Of Anaesthesia's Being a Spectrum Of Brain mentioning
confidence: 99%
“…Other methodologies indicate that brain responses are highly agent-specific [33,34]. Recent work using functional magnetic resonance imaging (fMRI) has suggested that with very slow propofol induction, a state is reached where the thalamocortical region of the brain becomes an 'island' of activity, apparently separated from sensory input, and that this is associated with loss of this region's response to auditory and nociceptive inputs [18]. However, other parts of the brain retained their response to these stimuli.…”
Section: Implications For Monitoringmentioning
confidence: 99%
See 1 more Smart Citation